Diversification of risk in Malaysian capital market analysis using composite and shariah market index performances - Shari, Aminah (2021)
The study aims to achieve three objectives. Firstly, the study investigates the daily comovement between risky assets (equity, bonds, commodity, and mutual funds) return and non-risky assets (treasury bills and money market funds) return towards composite and Shariah market indices for a capital market investment decision. Secondly, the study examines the dynamic co-movement trend between various risky assets and non-risky assets return towards composite and Shariah index to gain portfolio diversification benefits. Third, the study identifies the portfolio diversification benefits for risky and non-risky portfolios over different frequencies or investment horizons using analyses of Correlation-based, Multivariate-Generalized Autoregressive Conditional Heteroscedastic (MGARCH), Dynamic Conditional Correlations (DCCs), and Wavelet Coherence. The data was daily and spanned the period from 1 January 2007 to 6 February 2019. The study outcomes demonstrated that the co-movement between the risky and non-risky asset returns with composite and Shariah market indices varied timewise and was highly volatile. Additionally, the Maximal Overlap Discrete Wavelet Transform (MODWT) technique was implemented for study robustness. The study findings revealed that, first, the results of Correlation analysis show a significant co-movement relationship between risky asset and non-risky asset returns and composite and Shariah market indices. Notably, the extent to which the elements were correlated differed based on duration and scale. The correlation coefficient showed that all sectoral equity indices were significantly and positively correlated with composite and Shariah index returns. A positive correlation was also perceived under the commodities and money market funds with composite and Shariah indices, whereas a negative connection was observed in bonds and treasury bills. Second, MGARCH-DCC results show that co-movement between risky and non-risky asset returns is time-varying and highly volatile. In terms of volatility, the result indicates that all non-risky assets are less volatile than risky assets investment. From the co-movement analysis, the Malaysian sukuk and money market funds denoted negative and unconditional relationships with the composite and Shariah market indices as a positive indicator of diversification advantages. Moreover, the conditional correlation trend of sectoral equities tends to comove with composite and Shariah market indices implying low diversification advantages. Third, the same outcomes measured with the wavelet coherence analysis also revealed that the co-movement between sectoral indices and Shariah market returns were positive under the time and frequency domains. Regardless, the coherence in the index pair of sectoral indices and market returns rose at a low-frequency scale (64 to 256 and 256 to 1024 days) from 2007 to 2019. All assets eventually attained correlation and revealed minimal portfolio diversification advantages. The bond and money market funds also indicated weak links for most frequency scales, recommending favorable diversification for fixed-income Malaysian investors (portfolio diversification) through bonds and money market fund investments. However, in the long run, both commodities and mutual funds markets are correlated, implying minimum portfolio diversification advantages. Lastly, the findings corresponded across various econometrics technique estimations. The results also potentially benefitted investors, portfolio managers, retailers, and institutional investors to improve portfolio diversification advantages.